Parents' knowledge about the oral health care of oncological children - Bruna Rafaele Vieira PEDROSA; Walésia Laianny Leite MARTINS; Híttalo Carlos Rodrigues de ALMEIDA; Veronica Maria da Rocha KOZMHINSKY; Maria de Fátima Pessoa de Araújo SABINO; Kaline Maria Maciel de OLIVEIRA (Faculdade São Leopoldo Mandic, 2019)
ABSTRACT Objective: identifying the parents/guardians' knowledge about the oral health condition of oncological children assisted at the Pediatric Oncology Department of the Institute of Integral Medicine Professor Fernando Figueira. Methods: A cross-sectional study comprising a sample of 163 parents/guardians of children assisted at the Pediatric Oncology Department of the IIMP in the city of Recife, Pernambuco, applying a semi-structured form, tested with 10% of the sample in a pilot study. Results: Most of the parents/guardians were female subjects (87%) and patients' mothers (81%), between 25 and 34 years of age (44.8%), with a family income of a minimum wage (47%), educational level until elementary school (51.6%) and from the countryside of the state of Pernambuco (56%). Most of the children were male subjects (58.9%) with average age of 7.57 years, who had attended or stopped primary school (54.6%) and had been diagnosed with Acute Lymphoblastic Leukemia (57.7%) and treated with chemotherapy (92.6%). All parents considered important to have dental surgeons in the oncology department assisting the children in their oral hygiene. More than half of these parents reported knowing about how to avoid caries (63%) and, almost half of the children had never had a consultation with a dentist before (41.1%). Conclusion: Parents/guardians have information about oral health care, but they do not put it into practice.